Global Existence and Long-Term Behavior of a Nonlinear Schrödinger-Type Equation - Soltanov, K.N. (Український математичний журнал, 2015)
We study a global mixed problem for the nonlinear Schrödinger equation with a nonlinear term in which the coefficient is a generalized function. A global solvability theorem for the analyzed problem is proved by using the general solvability theorem from [K. N. Soltanov, Nonlin. Anal.: Theory, Meth., Appl., 72, No. 1 (2010)]. We also investigate the behavior of the solution of the problem under consideration. Вивчається глобальна мішана задача для нєлінійного рівняння Шрьодінгера з нєлінійним додаванням, в якій коефіцієнтом є узагальнена функція. Доведено теорему про глобальну розв'язність поставленої задачі на основі загальної теореми про розв'язність з [Soltanov K. N. Perturbation of the mapping and solvability theorems in the Banach space // Nonlinear Anal.: Theory, Meth. and Appl. - 2010. - 72, № 1]. Крім того, досліджено поведінку розв'язку задачі, що вивчається.